A CASE STUDY ON GRIDHRASI WITH SHEPHALI (NIRGUNDI) GHANAVATI - Waikar, Mugdha S.; Shinde, B. T. (International Journal of Research -GRANTHAALAYAH, 2021)
Ayurved is ancient and time tasted science. Till the date its principle remains unchange.The Ayurvedic science describes guideline for essential and harmful for long lasting healthy and happy life. (1) (2) Several disorders of biological system are produced by improper and changing lifestyle, busy professional life, long time sitting posture in office, continuous and over exercised in factories, changing food style all are responsible for vatavyadhi and specially Gridhrasi too. Gridhrasi is the one of the common disease. It has painful or Shoolpradhan condition which hamper the routine of life. It is occurs about three times as frequency in male as in the female as in the female sex. Gridhrasi is one of the Nanatmaj vyadhi and vata is is the main dosha in the Samprapti. It is the closely resemble with Sciatica which is characterised by low back pain and radiates towards leg mostly unilateral. The case study being presented of 42 years old female patient suffering from Vataj Gridhrasi with cardinal signs and symptoms of Gridhrasi are Ruk,toda,Stambh, and radiating pain in the leg in order of Sphik, Kati,Uru, Janu, Pad.Here Shaman chikitsa done with Shephali(Nirgundi) Ghanavati.(3)(4)